Posterior Lumbar Interbody Fusion with Preservation of Posterior Structures for Management of Lumbar Spondylolisthesis - Tarek Aly (Journal of Spine Practice)
Introduction: Successful posterior lumbar interbody fusion requires excessive removal of posterior spinal elements and distraction of neural structures. It also requires a large amount of bone graft. The authors have developed this technique to assess results of treatment of degenerative spondylolisthesis by posterior lumbar interbody fusion with preservation of posterior spinal elements and also to examine the safety and efficacy of the recapping  T-saw laminoplasty technique for the management of degenerative lumbar spondylolisthesis using posterior lumbar interbody fusion by interbody cages with preservation of posterior elements.